A Case of Cutaneous Leishmaniasis Presenting to the Emergency Department - Gordon A; Malik AN (Open Access Emergency Medicine)
Anne Gordon,1 Adrienne N Malik2 1The University of Kansas School of Medicine, Kansas, Kansas, USA; 2The University of Kansas Medical Center Emergency Department, Kansas, Kansas, USACorrespondence: Anne Gordon, The University of Kansas Medical Center, 3901 Rainbow Boulevard, Kansas, KS, 66160, USA, Email agordon5@kumc.eduAbstract: In this case, we describe a case of cutaneous leishmaniasis, a protozoan disease not typically found in the United States, that presented to our emergency department (ED). The diagnosis was confirmed by the Center for Disease Control and Prevention (CDC) through a polymerase chain reaction (PCR) sample from the presenting skin lesion. The patient was a 43-year-old woman with history of a bite by an unknown organism while traveling by foot through Panama. She presented with a large, ulcerated lesion on her lower left shin. She was admitted on suspicion of leishmaniasis, and physicians of several specialties initiated a broad laboratory workup, collected wound cultures, prescribed antibiotics, and surgically repaired the lesion. The rapid recognition of leishmaniasis allowed for the patient to begin treatment before the definitive diagnosis returned, emphasizing the importance of knowledge of worldwide diseases and their presenting features for the ED physician.Keywords: case report, rash, parasite, vector-borne disease